2012
DOI: 10.1007/s13187-012-0370-z
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Herbalists and Cancer Management in Kumasi, Ghana

Abstract: Cancer incidence rates are increasing in sub-Saharan Africa where traditional medical practitioners (TMPs) are involved in cancer management. Little is known about the specific role that TMPs play in cancer management in Ghana; we hypothesize that an understanding of the practices of TMPs with regard to cancer patients would help to enhance literacy about cancer amongst TMPs and would contribute to the diagnosis of cancer at earlier stages, by avoiding the detrimental delays while enlisting their help in certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 26 publications
2
38
0
Order By: Relevance
“…They lack knowledge of the early signs and symptoms of cancer and may diagnose cancer only when there is a visible mass, ulceration, or bleeding from advanced disease. 19 Travel has been documented in several studies as a barrier to cancer treatment. 20Y22 However, region of residence was not strongly associated with survival in this study.…”
Section: Resultsmentioning
confidence: 99%
“…They lack knowledge of the early signs and symptoms of cancer and may diagnose cancer only when there is a visible mass, ulceration, or bleeding from advanced disease. 19 Travel has been documented in several studies as a barrier to cancer treatment. 20Y22 However, region of residence was not strongly associated with survival in this study.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to more systematic efforts, assessments are needed to determine the effectiveness of campaign programs in terms of women actually practicing BSE [66, 83] and seeking prompt medical attention when problems are detected. Since many women initially seek treatment from traditional healers, it will be important to integrate these healers into overall health care systems [72]. …”
Section: Discussionmentioning
confidence: 99%
“…In many cases, effective treatment is hindered by women initially seeking care from traditional healers [59, 63, 71, 72]. Cancer is often viewed as a disease of the spirit, and women often only seek conventional care when traditional treatment has failed to result in the desired effects [73].…”
Section: Access To Carementioning
confidence: 99%
“…However, our study found that only 12.2% of patients sought alternative therapies before or during organized cancer care [4, 17]. Indeed, given the low physician-to-patient ratio in Ghana, the relative omnipresence of traditional healers in the country, and the fact that alternative therapies are usually more affordable, less invasive, and involve more intimate patient-practitioner relationships, it would be expected that a high proportion of patients would seek alternative therapies [8, 16, 17, 19, 21, 23]. Our findings may reflect a shift away from the heavy involvement of traditional healers in the treatment of cancer conditions as a result of traditional healer educational programs [17].…”
Section: Discussionmentioning
confidence: 99%
“…Pathology infrastructure for detecting hormone receptor status is deficient [19]. Only two public hospitals -Korle Bu Teaching Hospital in Accra and Komfo Anokye Teaching Hospital in Kumasi- possess the necessary equipment and staff for cancer management [8, 17, 21]. Since both public hospitals are located in the southern, more urban regions of the country, many individuals must travel long distances at significant financial cost to seek diagnosis and treatment [21].…”
Section: Introductionmentioning
confidence: 99%